Reproduction of original photo. . In Cudillero, Asturias. F.l.t.r. : Bartolomé, ?, Blanco, Gonzáléz Entrialgo, del Val
Reproduction of original photo. In Cudillero, Asturias. F.l.t.r. : Bartolomé, ?, Blanco, Gonzáléz Entrialgo, del Val.